Development of REACT- Based Physics Braille Learning Module in Linear Motion - Safitri Wulandari; Winarti Winarti (Jurnal Pembelajaran Fisika, 2019)
This research aims to develop a valid and feasible physics braille module based on Relating, Experiencing, Applying, Cooperating, and Transferring (REACT) learning model in linier motion. This study used R&D design with a procedural model that modified from the 4-D model consisting of define, design, and develop. The methods used in collecting data in this study are from interview and questionnaire. This study has successfully developed a valid and feasible physics braille module based on REACT, with the average scores of 3.12 for content and 2.85 for media aspect. These results also supported by the inclusive teachers and students who gave positive responses.  Keywords: braille module, inclusive, linier motion, REACTDOI: http://dx.doi.org/10.23960/jpf.v7.n1.201905